Potencial fitotóxico, antifúngico e antioxidante de extratos foliares de Myrcia splendens (Sw) DC. (Myrtaceae) - Pontes, Flávia Cevithereza (2015)
During its evolutionary process, plants have developed biosynthetic pathways by which they produce and accumulate a wide variety of secondary compounds that receive this name because they are not directly involved in the primary processes of plant growth and development. Many of these secondary compounds are responsible for chemical protection of plants against pathogens, herbivores, competing plants, ultraviolet radiation and other environmental stresses. The production of secondary metabolites can vary quantitatively and qualitatively between individuals of the same species, between plants of different species, between organs, between stages of plant development and are under influences of environmental factors. Studies of the biological effects of these compounds represent an important tool for the development of more specific and natural pesticides that are less harmful to the environment, as well as drugs and natural preservatives for food. Myrcia splendens (Sw.) DC. is a tree species found in the Brazilian cerrado and there are few published papers dealing with this species and its secondary metabolites to act as potential natural pesticides, antioxidant and antifungal. The methodology for the extraction of secondary metabolites can determine the composition of extracts and influence the activity of them. In this sense, in the first chapter of this work investigations were carried out on the phytotoxic potential of extracts of M. splendens young leaves from two different extraction methodologies. The 2C extract had the highest overall phytotoxic activity, showing promise in the search phytotoxic substances. In the second chapter, we investigate the phytotoxic potential of extracts and fractions of mature leaves of M. splendens from the two extraction methods carried out and was identified one of the secondary metabolites possibly associated with the phytotoxicity of the most active fractions. 2B fraction had the highest total inhibitory activity and so was fractionated, resulting in 14 fractions, which were also tested in wheat coleoptile. The FM8 and FM9 fractions, which had inhibitory activity and sufficient income, were subjected to HPLC for isolation of major compound. Identification by NMR spectra revealed that the major compound is miricitrin (myricetin-3-O-rhamnoside). In the last chapter, the extracts of mature leaves of M. splendens were tested for their antioxidant potential based on their ability to react with the free radical DPPH (2,2-diphenyl-1-picrylhidrazila) and antifungal potential using the plant pathogenic fungus Alternaria alternata as the target species. Most of the extracts showed a strong antioxidant activity, especially those iv! ! extracted with more polar solvents. On the other hand, only one of the extracts (2B) showed inhibitory activity on mycelial growth of the phytopathogenic fungus tested.